2020
DOI: 10.3390/cells9061363
|View full text |Cite
|
Sign up to set email alerts
|

miR-23a-3p is a Key Regulator of IL-17C-Induced Tumor Angiogenesis in Colorectal Cancer

Abstract: MicroRNAs (miRNAs) have emerged as key players in tumor angiogenesis. Interleukin-17C (IL-17C) was identified to promote colorectal cancer (CRC) progression. Therefore, we aimed to investigate the effect of IL-17C on tumor angiogenesis, the involvement of miR-23a-3p in IL-17C signaling, and the direct target gene of miR-23a-3p in CRC. In vitro and ex vivo angiogenesis, a mouse xenograft experiment, and immunostaining were performed to test the effect of IL-17C on tumor angiogenesis. ELISA, quantitative real ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Dual [28][29,30] ↓ in tumor under immunotherapy [33] ↑ in serum [74] ↓ by FMT under DSS [27] NF-κB Promote [ ↑ [134] ↓ in colon [94] ↑ by FMT [27,94,95] IL-17 Promote [106,135][114,135] ↓ in CD4 + T cell [113] ↓ in colon [94] ↓ by FMT under DSS [75] IFNs Suppress (α, β) [122] Controversial (γ) [124,129,130] ↓ IFNAR1 [122] ↓ α, β in ileum under viral infection [131] ↓ γ in T cells under viral infection [132] ↓ β, γ in SI under T. gondii infection [60] ↑ γ by L. delbrueckii, S. thermophilus under DMH-induced CRC [133] ↓ γ by FMT under DSS [75] ↑, up-regulated; ↓, down-regulated; CRC, colorectal cancer; GF, germ-free; ABX, antibiotics cocktail; TNF, tumor-necrosis factor; FMT, fecal microbiota transplantation; DSS, dextran sulfate sodium; NF-κB, nuclear factor kappa B; P. anaerobius, Peptostreptococcus anaerobius; IL-1, interleukin-1; LP, lamina propria; SI, small intestine; T. gondii, Toxoplasma gondii; VSL#3, probiotic mixture; CD, Crohn's disease; IL-6, interleukin-6; UC, ulcerative colitis; LPS, lipopolysaccharide; IL-10, interleukin-10; IL-17, interleukin-17; IFNs, interferons; IFNAR, interferon-α/β receptor; L. delbrueckii, Lactobacillus delbrueckii; S. thermophilus, Streptococcus thermophilus; DMH, 1,2-dimethylhydrazine.…”
Section: Tnfmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual [28][29,30] ↓ in tumor under immunotherapy [33] ↑ in serum [74] ↓ by FMT under DSS [27] NF-κB Promote [ ↑ [134] ↓ in colon [94] ↑ by FMT [27,94,95] IL-17 Promote [106,135][114,135] ↓ in CD4 + T cell [113] ↓ in colon [94] ↓ by FMT under DSS [75] IFNs Suppress (α, β) [122] Controversial (γ) [124,129,130] ↓ IFNAR1 [122] ↓ α, β in ileum under viral infection [131] ↓ γ in T cells under viral infection [132] ↓ β, γ in SI under T. gondii infection [60] ↑ γ by L. delbrueckii, S. thermophilus under DMH-induced CRC [133] ↓ γ by FMT under DSS [75] ↑, up-regulated; ↓, down-regulated; CRC, colorectal cancer; GF, germ-free; ABX, antibiotics cocktail; TNF, tumor-necrosis factor; FMT, fecal microbiota transplantation; DSS, dextran sulfate sodium; NF-κB, nuclear factor kappa B; P. anaerobius, Peptostreptococcus anaerobius; IL-1, interleukin-1; LP, lamina propria; SI, small intestine; T. gondii, Toxoplasma gondii; VSL#3, probiotic mixture; CD, Crohn's disease; IL-6, interleukin-6; UC, ulcerative colitis; LPS, lipopolysaccharide; IL-10, interleukin-10; IL-17, interleukin-17; IFNs, interferons; IFNAR, interferon-α/β receptor; L. delbrueckii, Lactobacillus delbrueckii; S. thermophilus, Streptococcus thermophilus; DMH, 1,2-dimethylhydrazine.…”
Section: Tnfmentioning
confidence: 99%
“…IL-17 can also promote tumor proliferation via the MAPK/extracellular signal-regulated kinase pathway and angiogenesis by stimulating the production of VEGF. In addition to angiogenesis, IL-17 directly stimulates the migration of CRC cells, suggesting a role in the promotion of CRC metastasis and invasion [ 103 , 104 , 105 , 106 ].…”
Section: Microbiota Inflammatory Mediators and Crcmentioning
confidence: 99%
“…Recently, some studies have shown the interaction of miRNAs with other biomarkers, such as KRAS [ 89 , 90 ], and their consequent role in predicting treatment response to classical cytotoxic chemotherapy or targeted therapy (anti-epidermal growth factor receptor (EGFR) and anti-VEGF) [ 91 , 92 , 93 , 94 ].…”
Section: Micrornamentioning
confidence: 99%
“…An inhibitor of this miRNA is under evaluation for the treatment of hepatocellular carcinoma [ 97 ]. High levels of miRNA-203 have been correlated with oxaliplatin resistance [ 93 ], and the deregulation of other miRNAs, such as miRNA-10b [ 98 ], is associated with 5-fluorouracil (FU) and irinotecan resistance [ 99 ].…”
Section: Micrornamentioning
confidence: 99%
“…Accumulating evidences indicate that miRNA-23a may be a critical regulator in carcinogenesis and aberrant miR-23a expression has been detected in many cancers. 16 , 17 Advances in cancer research have highlighted the cancer-promoting function of miR-23a in regulating cell proliferation, apoptosis, EMT and angiogenesis progress 16 , 18 However, some recent studies reported that miR-23a is downregulated in certain cancer types, including nephroblastomas and osteosarcoma. 19 , 20 Another group of researchers showed that miR-23a can exhibit pro-apoptotic functions.…”
Section: Introductionmentioning
confidence: 99%